Fcγ receptor activation mediates vascular inflammation and abdominal aortic aneurysm development. Issue 7 (4th July 2021) - Lopez‐Sanz, Laura; Bernal, Susana; Jimenez‐Castilla, Luna; Prieto, Ignacio; La Manna, Sara; Gomez‐Lopez, Sergio; Blanco‐Colio, Luis Miguel; Egido, Jesus; Martin‐Ventura, Jose Luis; Gomez‐Guerrero, Carmen
Abstract: Background: Abdominal aortic aneurysm (AAA), a degenerative vascular pathology characterized by permanent dilation of the aorta, is considered a chronic inflammatory disease involving innate/adaptive immunity. However, the functional role of antibody‐dependent immune response against antigens present in the damaged vessel remains unresolved. We hypothesized that engagement of immunoglobulin G (IgG) Fc receptors (FcγR) by immune complexes (IC) in the aortic wall contributes to AAA development. We therefore evaluated FcγR expression in AAA lesions and analysed whether inhibition of FcγR signaling molecules (γ‐chain and Syk kinase) influences AAA formation in mice. Methods: FcγR gene/protein expression was assessed in human and mouse AAA tissues. Experimental AAA was induced by aortic elastase perfusion in wild‐type (WT) mice and γ‐chain knockout (γKO) mice (devoid of activating FcγR) in combination with macrophage adoptive transfer or Syk inhibitor treatment. To verify the mechanisms of FcγR in vitro, vascular smooth muscle cells (VSMC) and macrophages were stimulated with IgG IC. Results: FcγR overexpression was detected in adventitia and media layers of human and mouse AAA. Elastase‐perfused γKO mice exhibited a decrease in AAA incidence, aortic dilation, elastin degradation, and VSMC loss. This was associated with (1) reduced infiltrating leukocytes and immune deposits in AAA lesions, (2) inflammatory genes and metalloproteinases downregulation, (3) redox balance restoration, and (4) converse phenotype of anti‐inflammatory macrophage M2 and contractile VSMC. Adoptive transfer of FcγR‐expressing macrophages aggravated aneurysm in γKO mice. In vitro, FcγR deficiency attenuated inflammatory gene expression, oxidative stress, and phenotypic switch triggered by IC. Additionally, Syk inhibition prevented IC‐mediated cell responses, reduced inflammation, and mitigated AAA formation. Conclusion: Our findings provide insight into the role and mechanisms mediating IgG‐FcγR‐associated inflammation and aortic wall injury in AAA, which might represent therapeutic targets against AAA disease. Abstract : Our work suggests a pathogenic role of IgG IC interaction with activating FcγR present in infiltrating and VSMC during AAA formation. These results support the investigation of novel immunotherapeutic strategies targeting FcγRs and/or downstream molecules to inhibit humoral immune damage in AAA